Globalleşme sürecinde küçük ve orta boy işletmelerin dışa açılmalarındaki başlıca örgütlenme modelleri ve uygulama örnekleri - Türkmen, Mahmut (My University, 1999)
Small and middle sized organizations play a principle role in the economy of both developed and developing countries .These organizations, on are side , are supporters and completers of organizations continually .On the other side, They keep their characteristic of being an application area by being in harmony with the techology which is the original dynamics of development, with non- strick production,and with applicant tecniques depends on knowledge, small and middle sized organizations importence increase gradually. Globalization's process accelerates and strenghten its power.The world's markets approach to each otter by means of transportation computers, the world's sources flow into the countries which provide suitable choices for themselves and everybody's being in state of potential customer no matter where they live in take attention as globalization process source and result. The changing process make competence of countries and organizations not national or sectional, but global. In the field of global competence, all organizations should open up into the world and organize their actions according to this. However ,in the intense competence ,companying with Europe's strong small and middle sized organizations, it is very difficult for our small and middle sized organizations to be successful and stand alone. Instead of struggling alone with the global competence, small and middle size organizations which have functional problems like in production, finance, personel and export must be a power in one hand.Subsequently, with the coopeation of small and middle sized organizations which function in the same production area, sectional Abroad Trade Company model appeared.Sectional Abroad Trade Company aims to open small and middle sized organizations, which are in the import area, in the 6B frame, into world markets,expertise them in the abroad import, in this way to increase their chance of competence abroad and to make them function more efficiently. According to this idea, our thesis' aim is to explain the kentarodel of small and middle sized organizations, sectioral Abroad Trade Company, in every aspect and to explain small and middle sized organizations, obligation to open up into abroad, the problems they face by the influence of globallization.
Keywords: KOBİLER